2021
DOI: 10.1177/00111287211047538
|View full text |Cite
|
Sign up to set email alerts
|

Mothering Through Mental Illness: Exploring the Experiences of Motherhood for Criminally Involved Women on Mental Health Probation

Abstract: As the number of criminally involved women has increased substantially over several decades, the prevalence of mothers impacted by criminal justice involvement has also increased. The current paper seeks to examine a specific subset of these criminally involved mothers—those with significant and long-term mental illness. This study explores how these women describe their experiences mothering through semistructured qualitative interviews with 48 women on a specialty mental health caseload in Maricopa County, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…This finding augments previous research in parents with broader experiences of SMI, highlighting the influence of shame on parents' sense of relationship security (Chan et al, 2019;Montgomery et al, 2006;Tjoflåt & Ramvi, 2013). The centrality of fear and shame, particularly around parents' perceptions of the negative impact of psychosis on their children, also echoes findings seen in studies and reviews of parents who experienced SMI (Ackerson, 2003;Dolman et al, 2013;Harries et al, 2022;Mulvey et al, 2021). These findings parallel recent research suggesting that children of parents who experience SMI can experience inflated responsibility to support their parents (Strand et al, 2020;Villatte et al, 2022), which may contribute to parents' sense of shame.…”
Section: Discussionsupporting
confidence: 76%
“…This finding augments previous research in parents with broader experiences of SMI, highlighting the influence of shame on parents' sense of relationship security (Chan et al, 2019;Montgomery et al, 2006;Tjoflåt & Ramvi, 2013). The centrality of fear and shame, particularly around parents' perceptions of the negative impact of psychosis on their children, also echoes findings seen in studies and reviews of parents who experienced SMI (Ackerson, 2003;Dolman et al, 2013;Harries et al, 2022;Mulvey et al, 2021). These findings parallel recent research suggesting that children of parents who experience SMI can experience inflated responsibility to support their parents (Strand et al, 2020;Villatte et al, 2022), which may contribute to parents' sense of shame.…”
Section: Discussionsupporting
confidence: 76%
“…It may be difficult for women to navigate these double standards and unfair, gendered treatment as a result of the implicit values of their providers. However, some research suggests the best way for women with mental health illness to get their needs met in various systems is to form strong relationships with their providers who can advocate on their behalf (Mulvey, 2013). Rehabilitation practitioners can educate team members on inpatient units to recognize their different sociocultural attitudes and treatment toward women when they act out due to these double standards to prevent punitive treatment of women in this area.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of remission also tends to be longer for women regardless of diagnosis (Schimmele et al, 2009). In addition, women typically express different treatment needs than men with mental health illness, particularly in the areas of trauma, sexual health, relationships, motherhood, and in forensic settings (Mowbray et al, 2003; Mulvey, 2013). Another study found that women with mental health illness in forensic settings appear to face added levels of social control in the probation and mental health systems within which they interface (Mulvey, 2013).…”
Section: Gender Issues In Mental Health Illnessmentioning
confidence: 99%
“…At the time of data collection, the SMI caseload had the ability to serve up to 680 SMI probationers at capacity (Maricopa County Adult Probation Department, 2013). Probationers on the caseload were assigned to 1 of 17 different SMI caseload officers who each supervised an individual caseload under the direction of two supervisors (Mulvey, 2013). The sizes of the SMI unit caseloads were capped at 1:40.…”
Section: Methodsmentioning
confidence: 99%